An Analysis of Protest Posters on RUU Pilkada Demonstration: A Landry Bourhis Linguistic Landscape Study: A Landry Bourhis Linguistic Landscape Study - Mochamad Riza Fahlivi; Fitri Rakhmawati; Khristianto; Sulasih Nurhayati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines how language choice in protest posters functions informatively and symbolically during demonstrations opposing the RUU Pilkada decision of Indonesia’s Constitutional Court in 2024. Employing the linguistic landscape framework established by Landry and Bourhis (1997), this study examines protest posters as public texts that signify political identity, power dynamics, and ideological stances. The data consist of 38 protest posters collected from the social media platform X using the hashtag #KawalPutusanMK. These posters were categorized into three language types: monolingual Indonesian, monolingual English, and bilingual Indonesian–English. Qualitative textual transcription and interpretive analysis were employed to examine the posters’ linguistic functions. The results show that monolingual Indonesian dominates the dataset (68.42%), followed by monolingual English (23.68%) and bilingual posters (7.89%). Indonesian is primarily used to communicate directly with local audiences and to construct a shared national political identity. In contrast, English and bilingual language choices are used strategically to frame local political criticism within global discourses of democracy, power, and human rights, which attracts greater attention in digital circulation. The results further indicate that protest posters mainly articulate power relations and ideological orientations, demonstrating how language is used to challenge political authority and express resistance across both physical and online spaces. This study contributes to linguistic landscape research by highlighting the role of temporary protest posters as strategic communicative resources in contemporary Indonesian political activism.